COVID-19 PANDEMIC AND MATERNAL HEALTH SERVICES IN PLATEAU STATE, NIGERIA - Alubo, Ogoh; Hunduh, Anande; Otache, Emmanuel (African Journal of Social and Behavioural Sciences, 2025)
Nigeria’s high maternal mortality rate remains a pressing public health issue. Although multiple interventions have been implemented, improvements have been modest. The emergence of COVID-19 further disrupted the healthcare system, redirecting resources and impacting essential services, including maternal care. This study investigated the impact of the COVID-19 pandemic on maternal health service delivery across primary, secondary, and tertiary care levels in Plateau State, Nigeria. It also assessed patient flow patterns during the pandemic compared to the pre-COVID period. The study was guided by Andersen’s Behavioural Model of Health Services Use (1968). A cross-sectional survey design and mixed-methods approach were employed. Using multistage sampling, 296 service users and 75 service providers were selected from health facilities across the three levels of care to participate in the study. Data were collected through structured questionnaires. Maternal services largely remained available during the pandemic. However, there was a notable decline in service utilisation due to movement restrictions, fear of infection, and facility-imposed limits on patient numbers. Temporary closures of some health centres were reported following confirmed COVID-19 cases. Although patient flow has since improved, many now face financial barriers to accessing care. While service availability was maintained during the pandemic, access was significantly constrained. With the resumption of routine healthcare, cost has become a primary barrier to maternal service utilisation. Addressing these financial constraints is crucial for improving maternal health outcomes in the post-pandemic period. The authors recommended emergency health system strengthening, socioeconomic support for vulnerable groups and capacity building for health workers: